Notes on the nesting habits of the Common Gallinule, Gallinula galeata (Lichtenstein, 1818) (Gruiformes, Rallidae) - Navega-Gonçalves, Maria Eliana Carvalho (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2021)
The Common Gallinule, Gallinula galeata, is a bird from humid areas, commonly found in almost entire Brazil. Between March and April 2019 I observed and described two nests built by the species in the Rua do Porto Park, in the city of Piracicaba, São Paulo state. The first nest was built on the water, near lakeshore vegetation and partially hidden by it, while the second, built on a sandbank in the lake, was exposed. Both were made of similar materials, with a predominance of vegetable branches of varying thickness, as well as tree bark, grasses, mosses, roots, leaves and fruits. Plastic material was found in both. I selected 60 images of nests of the species available on the WikiAves website – a Brazilian online platform for sharing ornithological records– for comparison with the ones that I observed. The analyses showed a variety of materials used in the nest building, as well as different nesting sites, both in aquatic and terrestrial environments, suggesting phenotypic plasticity. The proper park management, which aims at the conservation of nesting sites and resources, is essential to the survival of this and other birds in anthropized environments.